2000
DOI: 10.1017/s0021859699007352
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation strategy, nitrogen application and fungicide control in winter wheat on a sandy soil. I. Yield, yield components and nitrogen uptake

Abstract: A three factor experiment with winter wheat (Triticum aestivum L.) was carried out during two years on a coarse sandy soil in Denmark. The factors comprised four irrigation strategies including no irrigation, three nitrogen levels providing 67, 83 or 100% of the recommended nitrogen rate, and two strategies for control of leaf diseases (with and without fungicides). Different varieties were used in the two years, Pepital in the first year and Hussar in the second year. Mildew dominated the trial in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 20 publications
9
39
1
1
Order By: Relevance
“…This was a synergistic response to high N and fungicide because the response was greater than the sum of responses for a high N rate (170 vs. 100) and inclusion of fungicides (no fungicide vs. three applications), or 0.48 and 0.67 Mg ha -1 , respectively. The synergism between N and fungicide has been reported in the literature, but the synergistic yield improvements have not been as great or consistent as those presented in this study, and most are reported from environments that traditionally practice intensive wheat management (Ruske et al, 2003a;Olesen et al 2000;Walters and Bingham, 2007;Delin et al 2008). In contrast, Olesen et al (2003b) reported yield increases with N rates and fungicide applications, but the study did not show any interaction between N application rate and fungicide.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…This was a synergistic response to high N and fungicide because the response was greater than the sum of responses for a high N rate (170 vs. 100) and inclusion of fungicides (no fungicide vs. three applications), or 0.48 and 0.67 Mg ha -1 , respectively. The synergism between N and fungicide has been reported in the literature, but the synergistic yield improvements have not been as great or consistent as those presented in this study, and most are reported from environments that traditionally practice intensive wheat management (Ruske et al, 2003a;Olesen et al 2000;Walters and Bingham, 2007;Delin et al 2008). In contrast, Olesen et al (2003b) reported yield increases with N rates and fungicide applications, but the study did not show any interaction between N application rate and fungicide.…”
Section: Resultssupporting
confidence: 48%
“…The Lucan 2010 field site showed a reduction in spike density at the higher N rate, but this may attributed to a measurement error; counts were made after harvest, and the 170 kg ha -1 N rate plots were lodged more compared to the lower N rates, and thus some wheat stems that produced a spike of grain may not have been counted. High N rates have been found to increase spike density in spring wheat (Campbell et al, 1977) and in winter wheat (Olesen et al, 2000), although it must be applied early in the season to retain tillers (Spiertz and De Vos, 1983;Shah et al, 1994).…”
Section: Nitrogen Rate × Fungicide Interaction Effect On Winter Wheatmentioning
confidence: 99%
“…However, as stated by Jin et al (1999), extreme irrigation results in reduced efficiency in water use by crops, whereas effective water use efficiency leads to higher yields. Similarly, Olesen et al (2000) showed that the impacts of irrigation on wheat crops are almost entirely due to increased transpiration, while water use efficiency and the harvest index remain unaffected.…”
Section: *Wheatmentioning
confidence: 97%
“…Angus and Fisher 1991, Esala 1991, Peltonen 1995, Olesen et al 2000, Petersen 2004, Pedersen and Jørgensen 2007. The crop water availability is dependent on the field's site-specific water retention properties (Asseng et al 2001, Timlin et al 2001, Hakojärvi et al 2013) and the current growing season precipitation , Sadras et al 2012, Basso et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…When applying the nutrients this way, the synchrony between nitrogen availability and crop nitrogen demand , Shanahan et al 2008, Hancock et al 2011 can be enhanced and the threat of water soluble nutrients leaching to water systems can be decreased , Barberi et al 2008, Singh et al 2008, Basso et al 2011, Walsh et al 2013). Many studies have used split applications with predefined application rates (Esala 1991, Peltonen 1995, Olesen et al 2000, Asseng et al 2001, Kuisma 2002, Singh et al 2008, Basso et al 2009, Basso et al 2011, Hancock et al 2011) but observing the current growth conditions in defining the second application rate has also been suggested (Asseng et al 2001, Hakojärvi and Hautala 2010, Basso et al 2011, Walsh et al 2013. In these studies the current nitrogen status of the crop has been found to be an important measure but the information on crop water or stress status has also been found to be necessary for a successful nutrient prescription (Angus and Fischer 1991, Timlin et al 2001, Fitzgerald et al 2006, Jorgensen and Jorgensen 2007, Basso et al 2013, Walsh et al 2013).…”
Section: Introductionmentioning
confidence: 99%